What you wear can change your life - Woodall, Trinny; Constantine, Susannah; Mathews, Robin (London Weidenfeld & Nicolson, The Orion Publishing Group Ltd, 2004)
Trinny & Susannah have advised and dressed more than 3,000 women. They know instinctively the finer points and secrets of looking good. All their advice is presented in this book, whether it is something simple like knowing when to add a touch of blusher to a winter face or something more dramatic like changing the colour of your hair. They show how to choose the colours that suit you best, what underwear to buy, how to store clothes and how to revamp your wardrobe at no cost. They recommend beauty and makeup products and cover dressing for pregnancy. They give valuable hints on choosing accessories (handbags, shoes, belts, hats, jewellery) and travelling, including how to pose to best advantage in those holiday photographs. --Publisher's description.
1. Defining your shape -- 2. Underwear -- 3. Colour -- 4. Culling -- 5. Accessories -- 6. How to increase your wardrobe -- 7. Storage 8. Beauty -- 9. Makeup -- 10. Hair -- 11. Travelling -- 12. Pregnancy.
TV tie-in.
At head of title: Trinny and Susannah.
Keywords: Clothing and dress; Beauty, Personal